1986
DOI: 10.1007/bf01036742
|View full text |Cite
|
Sign up to set email alerts
|

Ecotypic variation in root respiration rate among elevational populations ofAbies lasiocarpa andPicea engelmannii

Abstract: Small trees ofAbies lasiocarpa (Hook.) Nutt. andPicea engelmannii Parry were collected along two elevational transects in the central Rocky Mountains, and the effects of low temperature on their root respiration activity were measured after growth in cool and warm soil temperature treatments.Picea engelmannii roots respired significantly faster than those ofA. lasiocarpa, and trees of both species collected from high elevations respired significantly faster than those from lower elevations. The mean Q and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Tjoelker et al (1999a) compared the root respiration rates of five cold-grown (18\12mC) and warm-grown (30\24mC) boreal tree species at a set measuring temperature (18mC) ; warm-grown plants exhibited root respiration rates that were 50-74% of those exhibited by the cold-grown plants. Moreover, acclimation was not evident in roots of two Picea species (Sowell & Spomer, 1986 ;Weger & Guy, 1991) or Abies lasiocarpa (Sowell & Spomer, 1986). Similarly, whereas acclimation to changes in growth temperature results in near-perfect homeostasis in Citrus volkameriana in wet soils, no acclimation occurs in roots of the same species growing in dry soils (Bryla et al, 1997).…”
Section:        mentioning
confidence: 94%
See 2 more Smart Citations
“…Tjoelker et al (1999a) compared the root respiration rates of five cold-grown (18\12mC) and warm-grown (30\24mC) boreal tree species at a set measuring temperature (18mC) ; warm-grown plants exhibited root respiration rates that were 50-74% of those exhibited by the cold-grown plants. Moreover, acclimation was not evident in roots of two Picea species (Sowell & Spomer, 1986 ;Weger & Guy, 1991) or Abies lasiocarpa (Sowell & Spomer, 1986). Similarly, whereas acclimation to changes in growth temperature results in near-perfect homeostasis in Citrus volkameriana in wet soils, no acclimation occurs in roots of the same species growing in dry soils (Bryla et al, 1997).…”
Section:        mentioning
confidence: 94%
“…4), comparisons of rates in warm-grown and cold-grown plants at their respective growth temperatures (Sowell & Spomer, 1986) do not enable us to conclude whether respiration has acclimated. Partial acclimation might therefore have occurred in roots of Abies lasiocarpa (Sowell & Spomer, 1986), even though the measurements at the growth temperatures suggested otherwise.…”
Section:        mentioning
confidence: 99%
See 1 more Smart Citation
“…Smakman and Hofstra 1982;Bouma et al 1997;Covey-Crump et al 2002;Loveys et al 2003) or root segments of differing age or function (e.g. Higgins and Spomer 1976;Crawford and Palin 1981;Sowell and Spomer 1986;Weger and Guy 1991;Zogg et al 1996;Pregitzer et al 1997Pregitzer et al , 1998Burton et al 2002;Comas and Eissenstat 2004). Recent studies with leaves have shown that the Q 10 of mature fully expanded leaves is higher than that of immature leaves (A Armstrong, OK Atkin unpublished data).…”
Section: Leaves V Rootsmentioning
confidence: 99%
“…However, there is actually a rather wide range in reported Q "! values for roots of tree species, with most values ranging from 2 to 3 (2.7 (Cox, 1975), 1.9-2.1 (Cropper & Gholz, 1991), 1.5-3.0 (Lawrence & Oechel, 1983), 2.0 (Sowell & Spomer, 1986), 2.7 , 2.1 , 2.0 (Ryan et al, 1996), and 2.0 ).…”
Section:  mentioning
confidence: 99%